2017
DOI: 10.1111/bjh.14603
|View full text |Cite
|
Sign up to set email alerts
|

The unique immunological features of heparin‐induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT) is a serious drug reaction that leads to a decrease in platelet count and a high risk of thrombosis. HIT patients produce pathogenic immunoglobulin G (IgG) antibodies that bind to complexes of platelet factor-4 (PF4) and heparin. HIT immune complexes crosslink Fc-receptors resulting in platelet and monocyte activation. These events lead to the release of procoagulant chemokines and tissue factor, which together create an intensely prothrombotic state. HIT represents an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 103 publications
0
26
0
Order By: Relevance
“…Heparin is known to activate platelets upon repeated administration [ 23 ]. It has been shown that the binding of heparin to PF4 induces a conformational change of the protein, leading to the exposure of a neo-epitope that induces the production of anti-PF4/heparin antibodies [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heparin is known to activate platelets upon repeated administration [ 23 ]. It has been shown that the binding of heparin to PF4 induces a conformational change of the protein, leading to the exposure of a neo-epitope that induces the production of anti-PF4/heparin antibodies [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Immunologically, type II HIT represents an atypical response with both T cell-dependent features represented by formation of antibodies to PF4-heparin complexes 6 and a T cell-independent mechanism as suggested by lack of a memory response upon heparin re-exposure. 7 For the remainder of the text, type II HIT will be referred to as HIT.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to type I, type II HIT is an immune‐mediated disorder caused by antibody formation (usually IgG) to platelet factor 4‐heparin complexes (anti–PF4‐heparin) which subsequently bind to either FcγRIIA receptor on platelets leading to their activation or on monocytes leading to tissue factor expression which facilitates platelet activation by thrombin, or to the glycosaminoglycan (GAG) molecules on the surface of platelets and endothelial cells . Immunologically, type II HIT represents an atypical response with both T cell‐dependent features represented by formation of antibodies to PF4‐heparin complexes and a T cell‐independent mechanism as suggested by lack of a memory response upon heparin re‐exposure . For the remainder of the text, type II HIT will be referred to as HIT.…”
Section: Introductionmentioning
confidence: 99%
“…The immune response in HIT is atypical: (i) anti‐PF4–heparin IgG antibodies are produced at the same time as IgM and IgA, as early as 5 days after heparin exposure ; (ii) anti‐PF4–heparin antibodies become undetectable 3 months after heparin administration ; and (iii) repeated heparin exposure does not usually elicit HIT recurrence, implying a lack of immune memory . Both T‐cell‐dependent and T‐cell‐independent immune mechanisms are probably important in HIT . Previous studies have shown HIT patients possess T cells with PF4–heparin‐specific T‐cell receptors , and murine models have demonstrated CD4 + T cells are necessary for the production of anti‐PF4–heparin antibodies .…”
Section: Introductionmentioning
confidence: 99%